The refinancing of Cimpor- Case study - Cruz, Ana Maria Furtado adao e Silva (2015)
The present case is about the refinancing of Cimpor, a highly profitable Portuguese cement group that encounters a set of obstacles in its debt restructuring. The case is intended to be used in a Corporate Finance class and is divided in three distinct parts: a case A which presents a detailed description of the internal and external events that increased Cimpor’s refinancing risk, a case B which informs the audience of the outcome of the refinancing process, and a Teaching Note with suggested questions and answers to be used in class. Key words: